Surgical Management for Chronic Exertional Compartment Syndrome of the Leg: A Systematic Review of the Literature - Campano, Dominic; Robaina, Jose A.; Kusnezov, Nicholas; Dunn, John C.; Waterman, Brian R. (Arthroscopy, 2016)
To review published literature to characterize the at-risk demographic, operative indications, surgical techniques, functional outcomes, and reoperation and complication rates after operative management of chronic exertional compartment syndrome (CECS) of the lower leg. We searched PubMed, Embase, Cochrane Database, and CINAHL (Cumulative Index to Nursing and Allied Health Literature) through February 1, 2015, using the terms “chronic exertional” and/or “exercise induced compartment syndrome.” The inclusion criteria were studies of Level I to IV evidence in English, published in 1970 or later, involving human subjects, reporting clinical outcomes of operative management of CECS of the lower leg, including at least 5 patients, and having follow-up of at least 80% and 6 months. Among the 204 original articles, 24 primary studies with 1,596 patients met the inclusion criteria. The mean age was 26.6 years (standard deviation, 8.9 years), and the majority of patients were male patients (70%). The total study population mostly comprised military service members (54%) and athletes (29%). Of the athletes, 83% were recreational; 9% were college level; and 8% were either national, international, or professional. The most commonly involved compartment was the anterior compartment (51%; 95% confidence interval [CI], 48.6% to 52.3%), followed by lateral (33%; 95% CI, 31.4% to 34.9%), deep posterior (13%), and superficial posterior (3%). The cumulative posterior involvement rate was 16% (95% CI, 15.1% to 17.8%). Mean follow-up was 48.8 months (standard deviation, 22.1 months; 95% CI, 47.1 to 50.5 months). Six percent underwent revision surgery. The overall complication rate was 13% (due to postoperative neurologic dysfunction, infection, and so on). Primary operative management of lower-extremity CECS was successful in approximately two-thirds of all young athletic patients, and 84% were satisfied with their surgical outcomes at short- to mid-term follow-up. Open fasciotomy remains the predominant surgical technique, although its comparative efficacy relative to newer endoscopic or other minimally invasive techniques is not currently known. These data may be used to guide the orthopaedic community on accurate preoperative counseling and benchmark patient outcomes for future quality-improvement initiatives. Level IV, systematic review (studies ranging from Level I to Level IV).